Organic Selenium Reaches the Central Nervous System and Downmodulates Local Inflammation: A Complementary Therapy for Multiple Sclerosis? - Toledo, Juliana Helena dos Santos de; Fraga-Silva, Thais Fernanda de Campos; Borim, Patrícia Aparecida; de Oliveira, Larissa Ragozo Cardoso; Oliveira, Evelyn da Silva; Périco, Larissa Lucena; Hiruma-Lima, Clélia Akiko; de Souza, Adriana Aparecida Lopes; de Oliveira, Carlos Alberto Ferreira; Padilha, Pedro de Magalhães; Pinatto-Botelho, Marcos Felipe; dos Santos, Alcindo Aparecido; et al. (Frontiers in Immunology, 2020)
Multiple sclerosis (MS) is an inflammatory and demyelinating disease of the central nervous system (CNS). The persistent inflammation is being mainly attributed to local oxidative stress and inflammasome activation implicated in the ensuing demyelination and axonal damage. Since new control measures remain necessary, we evaluated the preventive and therapeutic potential of a beta-selenium-lactic acid derivative (LAD-βSe), which is a source of organic selenium under development, to control experimental autoimmune encephalomyelitis (EAE) that is an animal model for MS. Two EAE murine models: C57BL/6 and SJL/J immunized with myelin oligodendrocyte glycoprotein and proteolipid protein, respectively, and a model of neurodegeneration induced by LPS in male C57BL/6 mice were used. The preventive potential of LAD-βSe was initially tested in C57BL/6 mice, the chronic MS model, by three different protocols that were started 14 days before or 1 or 7 days after EAE induction and were extended until the acute disease phase. These three procedures were denominated preventive therapy −14 days, 1 day, and 7 days, respectively. LAD-βSe administration significantly controlled clinical EAE development without triggering overt hepatic and renal dysfunction. In addition of a tolerogenic profile in dendritic cells from the mesenteric lymph nodes, LAD-βSe also downregulated cell amount, activation status of macrophages and microglia, NLRP3 (NOD-like receptors) inflammasome activation and other pro-inflammatory parameters in the CNS. The high Se levels found in the CNS suggested that the product crossed the blood-brain barrier having a possible local effect. The hypothesis that LAD-βSe was acting locally was then confirmed by using the LPS-induced neurodegeneration model that also displayed Se accumulation and downmodulation of pro-inflammatory parameters in the CNS. Remarkably, therapy with LAD-βSe soon after the first remitting episode in SJL/J mice, also significantly downmodulated local inflammation and clinical disease severity. This study indicates that LAD-βSe, and possibly other derivatives containing Se, are able to reach the CNS and have the potential to be used as preventive and therapeutic measures in distinct clinical forms of MS.